Pembelajaran Pesantren Berbasis Luar Jaringan (Luring) Selama Pandemi Covid-19 - Ibnu Chudzaifah; Afroh Nailil Hikmah (IAIN Sorong, 2021)
The COVID-19 pandemic period began to shift and shake the order of the learning process that usually takes place, one example is face-to-face learning turning into online learning. Online features seem to be a substitute for offline or face-to-face learning such as schoology, whatsapp, google classroom, moodle, zoom meeting, and several other applications that support learning (Kahfi & Kasanova, 2020). This shift has also begun to create new challenges for the world of Islamic boarding schools, as we all know that Islamic boarding schools are educational institutions that implement a boarding school system. Usually the discipline of the students can be measured through the punctuality of coming to school on time, but now this is an obstacle for the kiai or the asatidz council regarding the learning evaluation process, especially if the students who carry out the learning process with the online system, many from the economy or lower class. those who live in areas that do not support the internet network. Likewise, it is rather difficult to control the students in carrying out activities such as compulsory worship and other circumcision, even though we all know that what is unique about the education system in pesantren is the transfer of knowledge from the kiai or the asatidz council. The focus of this research is the online learning process at the Roudlatul Khuffadz Islamic Boarding School, Sorong Regency. Therefore, the author uses a qualitative descriptive analysis method, namely research that produces descriptive data in the form of words or text and behavior, which can be observed from the subject itself (Kahfi & Kasanova, 2020). This was done to reveal facts about Islamic boarding school learning in the midst of the Covid-19 pandemic at the Raudlatul Khuffadz Islamic boarding school, where most Islamic boarding schools were closed or using an online system. Fraenkel and Wallen argue that qualitative research can reveal real events that occur in the field (Kahfi & Kasanova, 2020). The methods that I will use include: Interview or Interview, Observation and Documentation Methods From the results of the study, the authors conclude that: First, during the Covid-19 pandemic, the Roudlotul Khuffadz Islamic Boarding School continued to carry out learning as usual (outside the network) while still adhering to health protocols. Second), the obstacles faced by the Roudlotul Khuffadz Islamic Boarding School in learning during the pandemic are first, related to the equipment of medical devices for the prevention of Covid-19. Second, Infaq as one of the financial income of pesantren tends to decrease due to the impact of the guardians who are also affected by Covid-19 from an economic perspective.